Metal-Free Direct N-Benzylation of Sulfonamides with Benzyl Alcohols by Employing Boron Trifluoride–Diethyl Ether Complex - Pan, Jing; Li, Jia-qiang; Huang, Ruo-feng; Zhang, Xiao-hui; Shen, Hang; Xiong, Yan; Zhu, Xiang-ming (Synthesis, 2015)
N-Benzylation of sulfonamides with both primary and secondary benzyl alcohols by employing boron trifluoride–diethyl ether complex under mild reaction conditions has been developed, which is an environmentally benign and facile protocol for assembling a series of primary and secondary benzyl sulfonamides in yields up to 83%. In this coupling reaction, the beneficial role of water has been clarified in detail through control experiments.
Keywords: N-benzylation; sulfonamides; benzyl alcohols; boron trifluoride–diethyl ether complex; water